2014
DOI: 10.1021/nn405331t
|View full text |Cite
|
Sign up to set email alerts
|

Direct, Concurrent Measurements of the Forces and Currents Affecting DNA in a Nanopore with Comparable Topography

Abstract: We report direct, concurrent measurements of the forces and currents associated with the translocation of a single-stranded DNA molecule tethered to the tip of an atomic force microscope (AFM) cantilever through synthetic pores with topagraphies comparable to the DNA. These measurements were performed to gauge the signal available for sequencing and the electric force required to impel a single molecule through synthetic nanopores ranging from 1.0 to 3.5 nm in diameter in silicon nitride membranes 6-10 nm thic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
54
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(57 citation statements)
references
References 41 publications
3
54
0
Order By: Relevance
“…The first barrier, W fr , denotes work done opposing relative motion between the polymer and the pore and may be expected to depend upon the 'tightness of fit' of the monomer in the pore, while a key component of W adh is the difference between the solvation energies of the polymer with the pore interior and with the exterior solvent -a hydrophobic molecule will experience the interior of the CD pore as a more favourable environment than the aqueous bulk phase. Both Lulevich 37 and, more recently, Nelson et al, 18 have found the sliding of ssDNA within nanopores to be frictionless, although in both cases the pores they investigated (between 1 and 3 nm diameter) were significantly larger than the pore of a cyclodextrin (0.5-0.6 nm diameter for α-and β-CD). The phenomenon of solvation as a barrier to polymer unfolding has been observed previously in SMFS experiments as the Raleigh Instability, resulting on the observation of plateaus as individual polymers are pulled out of the globular conformation they adopt in a poor solvent.…”
Section: Contributions Of Solvation and Friction To Sliding Forcementioning
confidence: 93%
See 2 more Smart Citations
“…The first barrier, W fr , denotes work done opposing relative motion between the polymer and the pore and may be expected to depend upon the 'tightness of fit' of the monomer in the pore, while a key component of W adh is the difference between the solvation energies of the polymer with the pore interior and with the exterior solvent -a hydrophobic molecule will experience the interior of the CD pore as a more favourable environment than the aqueous bulk phase. Both Lulevich 37 and, more recently, Nelson et al, 18 have found the sliding of ssDNA within nanopores to be frictionless, although in both cases the pores they investigated (between 1 and 3 nm diameter) were significantly larger than the pore of a cyclodextrin (0.5-0.6 nm diameter for α-and β-CD). The phenomenon of solvation as a barrier to polymer unfolding has been observed previously in SMFS experiments as the Raleigh Instability, resulting on the observation of plateaus as individual polymers are pulled out of the globular conformation they adopt in a poor solvent.…”
Section: Contributions Of Solvation and Friction To Sliding Forcementioning
confidence: 93%
“…This is rather larger than the values of ΔG sl calculated using the simulated forces and spring constants reported by Lindsay and Williams 10,23 (31-33 kJ mol −1 ), but as noted above, the experimental data for the sliding of β-CD along ssDNA published subsequently 10 shows force plateaus of approximately 110 pN, corresponding to a ΔG sl of 67 kJ mol −1 which agrees with our prediction. Nelson et al 18 observed two classes of behaviour for ssDNA sliding in nanopores with dimensions from 1-2 nm: so-called "frictionless" and "stick-slip". These behaviours were associated with forces of either 12-13 pN or 40-80 pN respectively.…”
Section: Towards Single Molecule Polymer Sequencingmentioning
confidence: 99%
See 1 more Smart Citation
“…While NFS offers a compelling alternative to other force microscopes 288 for a number of investigations, there are also a number of interesting uses of nanopores in conjunction with AFM and laser optical tweezers. 258,284,[289][290][291][292][293][294] Nanopore sensing selectivity can also be improved without molecular recognition agent adjuncts by incorporating different sensing mechanisms that may rely on adding sensing elements to the conventional platform (Fig. 1b).…”
Section: Nanofluidic Sample Cellsmentioning
confidence: 99%
“…18,19 Recently ssDNA has been immobilized to a SPM tip to study the interaction between a nanopore and ssDNA molecules. 20 In our previously published work, we used a home built apparatus that applied the force sensing mechanism of SPM to bring a dsDNA-attached tip close to a nanopore in a customdesigned fluidic chamber. After the dsDNA was pulled into the nanopore by the electrostatic force around a nanopore, the dsDNA is lifted from the pore with controlled speed.…”
Section: Introductionmentioning
confidence: 99%